PENGEMBANGAN E-LKPD MATEMATIKA MATERI SUDUT BERELASI TRIGONOMETRI KELAS X DENGAN FORMAT EPUB - Rahma, Alda Novia (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2023)
E-LKPD is a learning tool used by teachers to increase student involvement. The purpose of this study was to develop ELKPD results for learning in mathematics epub format with trigonometry related angle material, test their effectiveness in learning, and to find out student reactions to the use of trigonometry epub. Trigonometry Epub is a LKPD containing related angle material that can be used on digital devices, such as computers, laptops, and cellphones. This research method is research and development using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research was conducted in class X at SMKN Winongan in the even semester of the 2022/2023 academic year. The results showed that Epub trigonometry was declared valid by experts with very good scores, Epub trigonometry was declared effective in learning with an average test score and students completed or reached KKM, student response results through the use of Epub trigonometry was 81.82% included in the good category. In general, trigonometry epub has appropriate criteria, can be used as a support for student learning processes that can be used independently or in groups.